PEMETAAN JALUR “PAKET WISATA PEDESAAN” DI DESA WISATA PENGLIPURAN, KECAMATAN BANGLI, KABUPATEN BANGLI - Mahagangga, I G. A. O.; Suryawan, I. B.; Nugroho, S.; Sudana, I P. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
The potential of such unique nature and culture in the village Penglipuran it is proper to be developed and introduced to the tourists so that rural communities receive economic benefits, such as the availability of additional jobs and increase income by providing services as a local tour guide, provision culinary, providing soulvenir typical village Penglipuran and receiving income in the form of receipts village onggos admission and parking. Businesses that can be taken is the form of making the tour packages of innovative rural to attract the number of tourists visiting the village Penglipuran and improving the quality of human resources supporting. To develop further Penglipuran village, Pengabdi team has managed to make the packaging countryside tour package entitled "Village Tracking Tour" and Penglipuran Rural Cycling tour "second package is already manifested in the form of brochures. Realization of two packets of agrotourism has been preceded by a series of activities such as: 1) justify trajectory tracking path and cycling (something to see, something to do and something to learn) that will be bypassed by tourists in the countryside Penglipuran village and surrounding areas, 2) how to make tour event (itinerary), 3) how to determine the cost and the price of travel and 4) creating rural tourism package packing in the form of brochures.